PENGADAAN PERALATAN KRIPIK SAYUR SEHAT UNTUK PRODUK UMKM DESA DUWET KECAMATAN TUMPANG KABUPATEN MALANG - Mahmudatul Himma; Achmad Zaini; Ayu Sulasari; Diana Poenamawati; Nilawati Fiernaningsih; Muhammad Muwidha (P3M Politeknik Negeri Malang, 2025)
This Community Service aims to provide assistance and training for MSMEs in Duwet Village, Malang Regency The abundance of vegetables in Duwet Village creates problems, such as potential waste and decreased selling value. To overcome this, the transformation of vegetables into healthy vegetable chips can be an effective solution. By turning vegetables into chips, it can increase the added value of products, reduce waste, and create healthy snack alternatives that are attractive to consumers. This community service activity is in the form of assistance to MSMEs in Duwet Village, Tumpang District, Malang Regency The procurement of food dehydrators can make a significant contribution to partners by: Improving the efficiency of the vegetable dehydration process. Maintain the quality of nutrition and texture of the product. Supporting the increase in the production capacity of vegetable chips. Ensure consistency of product quality on an ongoing basis.